Analysis of stamping crack in bake hardening steel. Issue 1 (1st December 2022) - Feng, Huixiong; Huang, Geng; Liu, Xueli; Li, Liejun
Abstract: The bake hardening steel can better solve the contradiction between stamping formability and dent resistance of steel plates due to the lower strength and higher formability during stamping, as well as the advantages of increased strength after coating and baking. However, bake hardened steel can suffer from cracking problems in the stamping process. In this paper, the mechanical properties and stamping properties of the bake hardening steel were tested, and the production process was also analyzed. The results showed that the material has aged due to the long storage time, decreasing elongation. The main reason for stamping cracks was the reduction of the amount of oil applied to the material anti-rust oil. When the material was stored for a long time, the anti-rust oil on the surface of the steel plate volatilized, resulting in cracks in the stamping. Based on the above research, the material delivery time was strictly controlled. The cracks disappeared by supplementing and oiling the materials that had been stored for more than five months. The stamping performance of the bake hardening steel is improved.